Relação entre o estado nutricional e a carga viral em PVHA internadas em um hospital universitário de Belém-PA - SANTOS, Samantha Natasha Pessoa dos (2023)
OBJECTIVES: To relate nutritional status and viral load in patients living with HIV / AIDS. MATERIALS AND METHOD: This is an observational, descriptive, cross-sectional study. Patients of both sexes with age equal to or greater than 20 years, from September to November of 2018 were included. Data were collected: current/estimated weight, estimated height/height, thumb adductor muscle thickness (TAMT) viral load and CD4+ T lymphocyte count. To determine the nutritional status, the calculations of the Body Mass Index (BMI) and the adequacy classification of the TAMT were performed. RESULTS: Of the 55 patients who participated in the study, 54.5% (n=30) were males and 45.5% (n = 25) females, with a mean age of 39 (SD+12.7) years , with a minimum of 21 years and maximum age of 66 years. As to the determination of nutritional status by the IMC indicator, 47.3% (n=26) were malnourished, 38.2% (n=21) with adequate weight, 9.1% (n=5) were overweight and 5,4% (n=3) presented obesity. The classification of TAMT adequacy was characterized by the majority with 76.4% (n=42) presenting some degree of depletion and 23.6% (n=13) not being classified with depletion. Of the 50 subjects who participated in the laboratory analysis, 60% (n=30) presented values above 10,000 copies/ml for viral load, and 64% (n=32) had CD50 lymphocyte counts of ≤ 200 cells/mm³, 32% (n=16) CD4 values from 201 to 499 cells / mm³, and only two patients had CD4 values ≥ 500 cells/mm³. CONCLUSIONS: It was observed that the majority of the participants were male, in relation to nutritional status, there was a predominance of depletion and malnutrition, mainly associated with high viral load and CD4 + T lymphocyte levels below 200 cells / mm³. While individuals with adequate weight, overweight and obesity presented better levels of CD4 + T lymphocytes and lower viral load, when compared to the group with malnutrition.